Intestinal Parasitic Co-Infection in Reaction and Non-Reaction Leprosy Patients of Dhanusha, Nepal - Singh, Saurav K.; Maharjan, Mahendra (Journal of Institute of Science and Technology, 2015)
Development of reaction in leprosy patients causes severe complication in treatment. In order to analyze the association between leprosy-reaction and gastrointestinal parasitic co- infection, 100 each leprosy patients with reaction and non-reaction were identified and their stool samples were microscopically examined. The overall frequencies of intestinal parasites observed were 33 percent protozoa and 5.5 percent helminths. Entamoeba histolytica and Giardia lamblia were most prevalent parasites in both group of leprosy-reaction and non-reaction patients. Trichomonas hominis, Strongyloides stercoralis and Ancylostoma duodenales were found only in leprosy-reaction patients. There was positive co-relation between intestinal parasitic co-infection and development of reaction in leprosy patients.Journal of Institute of Science and Technology, 2015, 20(1): 64-67